2017
DOI: 10.1111/jcmm.12992
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenetic determinants in Kawasaki disease: the haematological point of view

Abstract: Kawasaki disease is a multisystemic vasculitis that can result in coronary artery lesions. It predominantly affects young children and is characterized by prolonged fever, diffuse mucosal inflammation, indurative oedema of the hands and feet, a polymorphous skin rash and non‐suppurative lymphadenopathy. Coronary artery involvement is the most important complication of Kawasaki disease and may cause significant coronary stenosis resulting in ischemic heart disease. The introduction of intravenous immunoglobulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 63 publications
1
25
1
Order By: Relevance
“…Del et al [ 8 ] suggested that the formation of heterotypic platelet–leucocyte aggregates, which is dependent on platelet activation, and leucocyte–RBC–platelet aggregates could at least partially be associated with the release of pro-aggregating factors (e.g., arachidonate) and/or with changes in the expression of molecules on the cell surface, including P-selectin. This crosstalk between activated platelets and leucocytes operates through several systems, including the interaction of P-selectin with P-selectin glycoprotein ligand-1 (PSGL-1).…”
Section: Discussionmentioning
confidence: 99%
“…Del et al [ 8 ] suggested that the formation of heterotypic platelet–leucocyte aggregates, which is dependent on platelet activation, and leucocyte–RBC–platelet aggregates could at least partially be associated with the release of pro-aggregating factors (e.g., arachidonate) and/or with changes in the expression of molecules on the cell surface, including P-selectin. This crosstalk between activated platelets and leucocytes operates through several systems, including the interaction of P-selectin with P-selectin glycoprotein ligand-1 (PSGL-1).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, KD is the major cause of acquired heart disease in children in developed countries [ 13 ]. The etiopathogenesis of KD may be attributed to the combined effects of genetics, immunity, and infection [ 14 ]. Although the exact etiology of KD is still unknown, predicting KD is possible with molecular markers [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the clinical features, diagnosis and treatment of KD are well established, its pathogenesis has not been identified yet. Several lines of evidence suggest that an interplay between microbial infection and genetic predisposition serve a role in the development of the disease ( 5 7 ).…”
Section: Introductionmentioning
confidence: 99%